'There's just no flexibility': How space and time impact mental health consumer research. (27th March 2019) - Scholz, Brett; Gordon, Sarah; Bocking, Julia; Liggins, Jackie; Ellis, Peter; Roper, Cath; Platania‐Phung, Chris; Happell, Brenda
Abstract: Non‐consumer researchers collaborating with consumer researchers can benefit from greater relevance of research and improved congruence between research processes and health policy. As with all research collaborations, such partnerships are both constrained and facilitated by research ecosystems. However, it seems that collaborations with consumer researchers are impacted in particular ways by the research ecosystem. Drawing on ecological systems theory, this study aims to improve understandings of how ecological structures impact collaborations between non‐consumer and consumer researchers. Interviews were conducted with 11 non‐consumer researchers from a range of mental health disciplines about their experiences collaborating with consumer researchers. One theme developed through analysis of the data set related to the research ecosystem. Data from this theme were extracted and discursively analysed using the principles of discursive psychology. Findings emphasize distinct factors that influence collaborations at each level of the ecosystem, encompassing both local research culture and broader research systems. Findings suggest that external pressures (such as deadlines for funding applications, or bureaucratic processes) from the broader ecosystemic levels need to be challenged at the local collaboration level. Non‐consumer researchers might support collaborations through, for instance, working to create enhanced flexibility in research timelines, or making time for relationship building, thus fostering more meaningful collaborations.